Exploring Language Teacher Candidates’ Reflective Competence in Microteaching Evaluation Practices - Petra Kristi Mulyani; Tassanee Juntiya (Vision: Journal for Language and Foreign Language Learning, 2025)
This study examines language teacher candidates' reflective competence in critically evaluating peers' instructional practices and materials during microteaching. In language teaching contexts, limited research has examined the quality and depth of peer evaluation during microteaching, despite its role in bridging theory and practice. Data were collected from 12 teacher candidates through peer evaluation notes, instructional materials, and recorded teaching sessions. Using a qualitative design, the data were analyzed using thematic analysis, supported by triangulation with five supervisors. Findings reveal that teacher candidates predominantly engage in surface-level evaluation, emphasizing technical and procedural aspects rather than conceptual pedagogical reasoning. The study argues that significant gaps reflect limitations in pedagogical content knowledge and reflective practice, especially in implementing problem-based and project-based learning, process-oriented assessments, and communicative language teaching to foster interaction and meaning negotiation. A structured reflective microteaching cycle is proposed to strengthen language teacher candidates' reflective competence, comprising three stages of replan, reteach, and reobserve. The findings highlight the urgent need for quality education through systematic critical reflection and pedagogical reasoning in language teaching education.